Numerical modeling and CFD simulation of diffuser augmented dual vertical axis hydrokinetic Banki-Michell turbine - Nebiyu Bogale Mereke; Venkata Ramayya Ancha; Patrick Hendrick (Heliyon, 2024)
Hydrokinetic Banki turbines present an affordable, technically feasible, environmentally friendly technology. Their construction without requiring more expensive structures like diversion weirs, canals, forebay, and penstock, makes their initial investment much lower than commonly used horizontal Banki turbine of the same capacity. The possibility to install in the existing canals for Ultra Low Head applications is the additional motivating factor for this research. The system studied includes two Banki runners without internal shafts mounted vertically side by side surrounded by nozzle and diffuser structures. In the first scenario, Nozzle and then the Nozzle-diffuser augmented structures were separately studied to enhance the output of the runner for ultra-low head application, and the effects of each on the speed, pressure, and power output were analyzed. For the case of commonly used Banki, without nozzle and diffuser augmentation the speed for Ultra Low Head was minimum and determined to be 344 rpm, which is far below the recommended value of 800 rpm for safe operation at a flow rate of 1 m^3/s. In view of this, in the present study the enhanced speed on account of improvement was found to be 850 rpm and 1025 rpm for the design without and with diffuser assemblies respectively. Besides, the performance is seen to be improved by 7.6% with the diffuser as compared with the one without diffuser assembly. Detailed simulation results are presented and discussed: 3D ANSYS-FLUENT optimization result provided optimum number of blades for each runner to be 19 and with the optimum throat width in both cases as 202 mm. On account of the lack of any results reported so far for this innovative geometry, validation of the simulated results was carried out with reported results for the dual horizontal axis Banki turbines with good agreement.